Exploring the feasibility of combining transcutaneous electrical spinal cord stimulation and overground robotic exoskeleton for gait rehabilitation in patients with spinal cord injury - Algaba-Vidoy, Marina; Pérez-Nombela, Soraya; Megía-García, Álvaro; Montero-Pardo, Cristina; Redondo-Galán, Carolina; de los Reyes-Guzmán, Ana; Serrano-Muñoz, Diego; Gómez-Soriano, Julio; Del-Ama, Antonio J.; Moreno, Juan C. (Frontiers in Neurology, 2025)
IntroductionSpinal cord injury (SCI) is a traumatic condition that causes severe sensory and mobility impairments, including gait dysfunction. Combining exoskeleton-assisted gait training (EGT) with transcutaneous spinal cord stimulation (tSCS) may enhance motor recovery in SCI patients. This study explores the feasibility and immediate effects of combining these two neurorehabilitation strategies, without pursuing clinical benefits.MethodsWe present a 3-of-1 case series of incomplete SCI patients (AIS C-D) who participated in two walking sessions: tSCS-assisted gait, then combined with the robotic exoskeleton Exo-H3. Each session included three phases of 3 min each: before, during and after tSCS. Surface electromyography (EMG) was recorded to analyze muscle activation and the level of effort generated using root mean square (RMS) and integrated EMG (iEMG). Functional outcomes were assessed with the Timed Up and Go (TUG) test, Visual Analog Scale (VAS) for discomfort and fatigue and distance covered.ResultsImmediate effects varied among patients. Participant 1 showed increased muscle activation and effort without the Exo-H3 after tSCS, particularly in the Rectus Femoris (ReFe) muscle, along with improved TUG performance and walking speed. However, during the combined tSCS-Exo session, muscle activation did not decrease, but effort was significantly reduced, masking the tSCS effects seen without the exoskeleton. Walking speed and TUG also worsened. Participant 2 exhibited reduced RMS and iEMG in both conditions, especially in the ReFe, with no notable improvement in TUG score or distance covered. In contrast, Participant 3 appeared to benefit from both sessions, showing increased activation and exertion in the tibialis anterior and upper leg (biceps femoris and ReFe). TUG did not improve in the non-exoskeleton session after tSCS but showed significant improvement when combined with Exo-H3. None of the participants reported abnormal discomfort or fatigue beyond the levels typically associated with exoskeleton use.DiscussionThe combined use of tSCS and EGT appears technically feasible and safe, whereas the responses were highly individualized. Knee extensors muscles showed the greatest responsiveness to tSCS during gait. Synergistic effects may depend on the user’s proficiency with the exoskeleton. Further analysis and larger studies are needed to better identify SCI who may benefit the most.